The inflation of house prices : its extent, causes, and consequences - Grebler, Leo.; Mittelbach, Frank G. (Lexington, Mass. : Lexington Books, 1979)
This book is on the growth of house purchase and the income and wealth constrain on various group of buyers.
Includes bibliographical references and index.
oo 26/10/2018
Loans
Keywords: Housing; Inflation (Finance)